1990
DOI: 10.1111/j.1365-2982.1990.tb00031.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Motilin Variation During the Interdigestive and Digestive States in Man

Abstract: To evaluate the role of motilin in human physiology, we measured plasma motilin during the inter digestive and digestive states while recording antroduodenal contractile activity. In 24 healthy fasting subjects, 51 migrating periods of phase III activity were recognized, 42 of them started from the antral region and nine from the duodenum. A definite association was noted between circulating motilin and the gastric migrating motor complex. Significant peak elevations in plasma motilin were associated with phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 24 publications
2
10
0
Order By: Relevance
“…Our data, together with previous data, report an increase in motilin plasma levels prior to gastric phase III contractions, which questions the hypothesis that the strong antral contractions during phase III induce the release of motilin . Further evidence for this causality was given by Tack et al .…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Our data, together with previous data, report an increase in motilin plasma levels prior to gastric phase III contractions, which questions the hypothesis that the strong antral contractions during phase III induce the release of motilin . Further evidence for this causality was given by Tack et al .…”
Section: Discussionsupporting
confidence: 55%
“…The high motilin levels may decrease motilin receptor sensitivity. In fact, a refractory period for gastric stimulation by motilin has been suggested previously . Indeed, after a gastric phase III the MMC cycle duration in the gastroduodenal region is prolonged …”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Indeed, in humans, only phase III contractions with a gastric but not a small-intestinal origin are preceded by a motilin plasma peak (6,7). In addition, administering exogenous motilin to dogs and humans induces gastric phase III contractions (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…Motilin can be detected periodically during the interdigestive period, and can initiate the interdigestive migrating motor complex (Tack, 1992). The peripheral motilin mainly acts as the stimulatory factor for gastrointestinal motility and biliary contraction, while the intra-arterial injection of motilin can induce an antral contraction phase in a physiological dose-dependent manner (Boivin et al, 1990). It is previously reported that the motilin mRNA is expressed in the CNS of monkeys, dogs, cats, rabbits, rats and other animals (Xu et al, 2003).…”
Section: Discussionmentioning
confidence: 99%